2016
DOI: 10.1590/1807-3107bor-2016.vol30.0117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molar-incisor hypomineralization on oral health-related quality of life in schoolchildren

Abstract: This study evaluated the impact of molar-incisor hypomineralization (MIH) on oral health-related quality of life (OHRQoL) according to the perceptions of schoolchildren and their parents/caregivers. This cross-sectional study consisted of a sample of 594 schoolchildren between 11 and 14 years of age and their parents/caregivers who answered the questionnaires CPQ11-14ISF:16 and P-CPQ, respectively. The main independent variable of this study was MIH of the schoolchildren. Experience of dental caries, malocclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
103
2
24

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 32 publications
11
103
2
24
Order By: Relevance
“…An association was found between severe MIH and OHRQoL in the functional limitations domain of the CPQ 11‐14 , which addresses difficulties with chewing, sleep, and speech . In the previous study, a higher prevalence of more severe MIH lesions was observed (50.5%), which was different from the present results, in which these changes were uncommon (28.4%). The loss of dental structure increases the accumulation of biofilm and facilitates the transport of bacteria to dentin, thus aggravating sensitivity because there is greater exposure of dentinal tubules .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An association was found between severe MIH and OHRQoL in the functional limitations domain of the CPQ 11‐14 , which addresses difficulties with chewing, sleep, and speech . In the previous study, a higher prevalence of more severe MIH lesions was observed (50.5%), which was different from the present results, in which these changes were uncommon (28.4%). The loss of dental structure increases the accumulation of biofilm and facilitates the transport of bacteria to dentin, thus aggravating sensitivity because there is greater exposure of dentinal tubules .…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of MIH on OHRQoL was previously evaluated in 11‐ to 14‐year‐old Brazilian children using the CPQ 11‐14 , which is specific to this age group. The authors who applied the CPQ 11‐14 also observed an impact of MIH in the oral symptoms domain but only in individuals with severe lesions, such as post‐eruptive fractures . An association was found between severe MIH and OHRQoL in the functional limitations domain of the CPQ 11‐14 , which addresses difficulties with chewing, sleep, and speech .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the MIH global prevalence varies, mean 13.1% (Schwendicke et al, ), and damage caused to functionally essential teeth makes it a major public health problem (Schneider & Silva, ). MIH may impact on the well‐being of young patients in a crucial period of infant development (Dantas‐Neta et al, ; Leal, Oliveira, & Ribeiro, ). Moreover, currently, in the absence of identified cause(s), no risk prevention actions can be implemented (Silva, Scurrah, Craig, Manton, & Kilpatrick, ).…”
Section: Introductionmentioning
confidence: 99%
“…MIH constitutes a public health problem, with consequences that are not only health-related but also economic. MIH may impact on the well-being of young patients in a crucial period of infant development 15, 16 . The proposal for a single term “MIH” and the establishment of specific diagnosis criteria by consensus promoted and encouraged the multiplication and quality of research works, but some issues remain unresolved 11 .…”
Section: Introductionmentioning
confidence: 99%